Development without women is not development why gender matters to the Asian Development Bank. ([Manila] Asian Development Bank, 2019)
Gender equality and women empowerment are essential for meeting Asia and the Pacific aspirations of inclusive and sustainable development. Under Strategy 2030, ADB has committed to accelerate progress in gender equality. ADB is increasingly designing its projects to promote women economic empowerment; boost gender equality in human development, decision making, and leadership; reduce poverty of women; and strengthen women resilience to external shocks.
Keywords: Gender equality; Women economic empowerment; Electronic books